Did you draw what I wanted to say? Picture-Text Dynamics and Intersemiotic Translation in Roald Dahl’s Matilda - Echauri Galván, Bruno (Onomázein, 2019)
The present paper is an analysis of the illustrations of Roald Dahl’s Matilda (2016 [1988]) through the prism of intersemiotic translation. The main purposes of this study are to determine the type of relationships established between text and pictures in the novel and to identify how the illustrator represents some of its main topics, to wit: the importance of books and education, adults’ abuse of power, rebellion, and school mistreatment. In order to achieve these objectives, the paper analyzes the interrelation between several passages of the text and their corresponding illustrations. Subsequently, the study categorizes the different dynamics established between text and pictures and discusses how some procedures connected to Translation Studies can be aligned with the decisions taken by the illustrator when depicting the foregoing themes. As a result, the paper concludes that Matilda’s illustrations work as emphasizers of some of the messages Dahl intended to transmit to his readership when writing this book.